ARTIFICIAL INTELLIGENCE DALAM KESEHATAN DAN KESELAMATAN KERJA DI BIDANG KELISTRIKAN - Sofyan Mufti Prasetiyo; Apriwinda Rahmayani; Auli Melania (CV. Multi Kreasi Media, 2023)
Artificial intelligence has become one of humanity's greatest technological inventions. With artificial intelligence, human work becomes easier. Artificial intelligence can be a factor in progress in the electricity sector, especially in terms of security. One of the functions of developing artificial intelligence in Occupational Health and Safety (K3) is in detecting hazards, such as detecting workers who have not used Personal Protective Equipment (PPE) by using technology such as Neural Networks, Computer Vision, and Object Recognition or detecting land conditions that are will be used for Grounding with Fuzzy Logic. This is expected to reduce the risk of hazards in the work environment.